Intermittent hemodialysis is superior to continuous veno-venous hemodialysis/hemodiafiltration to eliminate methanol and formate during treatment for methanol poisoning - Zakharov, Sergey; Pelclova, Daniela; Navratil, Tomas; Belacek, Jaromir; Kurcova, Ivana; Komzak, Ondrej; Salek, Tomas; Latta, Jiri; Turek, Radovan; Bocek, Robert; Kucera, Cyril; Hubacek, Jaroslav A; et al. (Kidney international, 2014)
During an outbreak of methanol poisonings in the Czech Republic in 2012, we were able to study methanol and formate elimination half-lives during intermittent hemodialysis (IHD) and continuous veno-venous hemodialysis/hemodiafiltration (CVVHD/HDF) and the relative impact of dialysate and blood flow rates on elimination. Data were obtained from 11 IHD and 13 CVVHD/HDF patients. Serum methanol and formate concentrations were measured by gas chromatography and an enzymatic method. The groups were relatively comparable, but the CVVHD/HDF group was significantly more acidotic (mean pH 6.9 vs. 7.1 IHD). The mean elimination half-life of methanol was 3.7 and formate 1.6 h with IHD, versus 8.1 and 3.6 h, respectively, with CVVHD/HDF (both significant). The 54% greater reduction in methanol and 56% reduction in formate elimination half-life during IHD resulted from the higher blood and dialysate flow rates. Increased blood and dialysate flow on the CVVHD/HDF also increased elimination significantly. Thus, IHD is superior to CVVHD/HDF for more rapid methanol and formate elimination, and if CVVHD/HDF is the only treatment available then elimination is greater with greater blood and dialysate flow rates.
Keywords: hemodialyzační roztoky; dospělí; methanol; formiáty; Formates; Female; antidota; Renal Dialysis; hemodiafiltrace; Half-Life; Hydrogen-Ion Concentration; dialýza ledvin; Adult; ženské pohlaví; lidé; Methanol; Antidotes; Hemodialysis Solutions; poločas; rychlost toku krve; Blood Flow Velocity; prospektivní studie; Male; Aged; Czech Republic; Prospective Studies; Česká republika; lidé středního věku; Hemodiafiltration; senioři; mužské pohlaví; koncentrace vodíkových iontů; Middle Aged; Humans